A cohort study investigating a point source outbreak of Clostridium perfringens associated with consumption of roasted meat and gravy at a buffet on Mothering Sunday 2018, South West, England. (June 2020) - Packer, Simon; Day, Jane; Hardman, Peter; Cameron, Julia; Kennedy, Michael; Turner, Jonathan; Willis, Caroline; Amar, Corinne; Nozad, Bayad; Gobin, Maya
Abstract: In March 2018, Public Health England was alerted to an outbreak of gastrointestinal illness in persons who had eaten at a restaurant in the South West of England on Mothering Sunday. We aimed to determine the source of infection and control the outbreak. A retrospective cohort study was undertaken among all individuals who ate at the restaurant on March 11, 2018. Cases were defined as any person who consumed food from the restaurant and had diarrhoea or vomiting between 12:00 March 11, 2018 and 23:59 March 15, 2018. Data were collected using a secure electronic questionnaire. Descriptive, univariable and multivariable analyses were undertaken with odds ratios (OR) and 95% confidence intervals (CI) calculated for exposures. Clinical and food samples were collected for microbiological testing and molecular typing. The restaurant reported 293 people attending, 176 (60%) completed the survey and 146 (50%) provided sufficient information for inclusion in the analysis. Eighty-one persons met the case definition (attack rate 55.5%); eating from the roast meat buffet was associated with illness (OR: 7.80, 95% CI: 2.03–43.56). No single food item explained all the cases. Independent associations between consumption of gravy (adjusted OR (aOR): 5.35, 95% CI:2.21–12.93), lamb (aOR: 2.51, 95% CI:1.06–5.96), and eating during the later 16:00 sitting (aOR: 5.23, 95% CI:1.76–15.54) were identified. Clostridium perfringens enterotoxin was detected in clinical samples and the same strain of enterotoxigenic C. perfringens that was isolated from clinical samples was also detected in roasted lamb, beef and turkey. We found strong evidence for an outbreak of C. perfringens food poisoning associated with gravy and/or meat consumption. The data suggests cross-contamination between items, which increased over time. We recommend that health agencies ensure that restaurants serving roasted meat buffets adhere to minimum oven temperatures and take special measures to prevent food poisoning and cross contamination at the preparation and serving stage. Highlights: Fast multidisciplinary action essential to delineate an outbreak of food poisoning. Initial failures in food preparation can be easily amplified by cross contamination. Buffet restaurants need to take special measures during food service.